2021
DOI: 10.1007/s40615-021-01110-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Potential Occupational Exposure to COVID-19

Abstract: Background Nationwide, as of 20 June 2021, COVID-19 has claimed more than 599,000 lives and infected nearly 33 million people. Studies have shown that COVID-19 disproportionately affects some racial and ethnic minority groups. This study examined whether certain racial and ethnic groups were overrepresented in occupations with potentially high COVID-19 exposure risks, relative to their share in the total workforce. The study incorporates white collar workers, who to date have not gotten as much attention in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In their assessment of the early impacts on US industry employment, Gabe and Florida found occupations requiring close physical proximity and the most interaction with members of the public likely experienced employment declines during the first few months of the pandemic 19 . More recently, Asfaw found Black workers overrepresented within those occupations working close to one another and Hispanic workers lacking the ability to work from home using O*NET and 2020 US CPS employment data 20 . Employment changes were evident and variable during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their assessment of the early impacts on US industry employment, Gabe and Florida found occupations requiring close physical proximity and the most interaction with members of the public likely experienced employment declines during the first few months of the pandemic 19 . More recently, Asfaw found Black workers overrepresented within those occupations working close to one another and Hispanic workers lacking the ability to work from home using O*NET and 2020 US CPS employment data 20 . Employment changes were evident and variable during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, Asfaw found Black workers overrepresented within those occupations working close to one another and Hispanic workers lacking the ability to work from home using O*NET and 2020 US CPS employment data. 20 Employment changes were evident and variable during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, individuals from minority groups with lower job security and low-income experienced job loss [ 60 , 61 ], which might have led them to pursue informal jobs with enhanced exposure risk to COVID-19. Also, those who did not lose their job appear to fill jobs with a higher risk of COVID-19 contagion and exposure, with an inability to work from home, which also jeopardizes them [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that differential occupational exposure is one main contributing factor to racial disparity in COVID-19 associated outcomes [ 46 , 47 ]. Non-Hispanic Black residents, in addition to living in already resource-deprived neighborhoods, are more likely to work in industries that are not amenable to remote working, have less ability to physically distance themselves from others in the workplace, and have more frequent exposure to infections while at work compared to other racial groups [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%